Erotic Leonardo: Eroticism in Leonardo da Vinci’s Sketches - Casado-Chamizo, Sergio (Aisthesis, 2025)
Though dissected under countless lenses, Leonardo Da Vinci’s art continues to pulse with enigmatic work. This study ventures beyond familiar territory, unearthing potential erotic undercurrents within his sketches, anatomical studies, and paintings. It employs a multifaceted lens, weaving together threads of philosophy, aesthetics, and psychoanalysis to illuminate the subtle interplay of form and hidden psychology embedded within his works. More than mere discovery, this analysis seeks a critical revaluation. By incorporating gender-critical perspectives, it challenges established interpretations, offering a fresh and nuanced understanding of the master’s enduring legacy. This approach not only delves into underexplored territory but also invites broader conversations about representation, power, and the very nature of artistic expression.